ITeam : Putting the "I" Back into Team - E., William Perry (Addison-Wesley Professional, 2013)
This is the digital version of the printed book (Copyright © 2009). It will surprise few professionals working in software development today to read that teams and teamwork are critical ingredients of a global economy. Productivity, product development and release, and even a company's survival increasingly will depend on teams to solve business problems. What may come as a surprise -- and a wake-up call -- is that, in many businesses, teams are completely ineffective. One reason, posits William E. Perry in iTeam: Putting the "I" Back into Team, is that most organizations put too much emphasis on joint effort, removing responsibility, ownership, and reward from individuals appointed to teams. What typically results is dysfunctional, essentially leaderless, and lacking in motivation. Perry's call to put the emphasis back on individual responsibility among collaborating teammates is an urgent one. Decisions now made by management will more and more frequently be made and implemented by teams, making it necessary for organizations to ensure that the creativity and innovative methods of individuals be retained on teams. Through extensive team experience and interviews with hundreds of individuals who have spent thousands of hours in team meetings, Perry has identified the attributes of great teams and great teamwork. iTeam examines the ten biggest challenges standing between most teams and excellence and explores in depth the fifty best practices teams can employ to improve performance. Concluding that world-class teams comprise individuals who do what is right for their organization, and do what is right the right way, iTeam presents a clear, practical argument for building teams that have at their core a strong, proven leader who encourages and motivates team members to fulfill their team responsibilities. Topics include: Reengineering the Team Approach to Problem Solving The Top-Ten Challenges to Effective Teamwork Selecting a Team Leader Who Will Lead Defining Team Entrance and Exit Criteria Selecting Team Members for Specific Roles Building Trust Among Team Members Training Team Members to Accomplish Their Assignments Listening to the Voice of the Customer Breaking Down Silos Avoiding Groupthink Assuring That Team Efforts Are Successful Rewarding Individual Team Members Keeping Teamwork Competitive Emerging Team Practices and much more.